Life orientation and psychological distress in COVID recovered patients-the role of coping as a mediator - Ji, Yan; Yaseen, Faiqa; Sohail, Marva (Frontiers in Psychology, 2022)
Abstract The coronavirus disease (COVID-19) pandemic has not only brought the risk of death but has brought unbearable psychological pressures to the people. Mental health of COVID patients is expected to be affected by the continuous spread of the pandemic. This study aims to find the mediating role of coping styles in the relationship between life orientation and psychological distress among COVID recovered patients. It was hypothesized that: life orientation is likely to have a relationship with coping; coping is likely to have a relationship with psychological distress and coping is likely to mediate the relationship between life orientation and psychological distress among patients recovered from COVID. For this purpose, 378 COVID-10 recovered patients’ men (190) and women (188). Urdu translations of the Life Orientation scale revised, Brief Coping Orientation to Problem Experienced (COPE) and Impact of event scales were used to collect data. Results show that emotion-focused and avoidant coping mediate the relationship between life orientation and psychological distress. The research has implications for mental health practitioners and individuals dealing with health-related issues.